The Role Of Instagram Social Media As A Promotional Platform For UNESCO Global Geopark Ijen - Irmayanti, Irmayanti; Pribadi, Wikan; Rohaendi, Nendi (The International Journal of Business Review (The Jobs Review), 2024)
Purpose—Social media has become a powerful communication tool in promotion and marketing, particularly in the tourism industry. This study aims to identify the impact and effectiveness of using Instagram as a social media platform to promote the uniqueness, natural beauty, local culture, and environmental conservation efforts of Geopark Ijen, a UNESCO Global Geopark in East Java, Indonesia. The research addresses the problem of how social media can enhance the visibility and attractiveness of tourism destinations.Design/methods/approach–The research employs a qualitative descriptive methodology, presenting data clearly and comprehensively without conducting comparative analysis or examining relationships with other variables. Data is analyzed qualitatively, with findings presented in words and sentences.Findings–The research findings demonstrate that Instagram significantly contributes to promoting Geopark Ijen through attention-grabbing content that enhances its visibility as a prominent tourism destination in Indonesia. The study confirms that social media can effectively highlight the unique features and conservation efforts of Geopark Ijen, thereby attracting a wider audience.Research implications/limitations – The study's qualitative design limits the generalizability of the findings. The research does not compare the effectiveness of Instagram with other social media platforms or marketing strategies, which could be explored in future studies. Additionally, the study is constrained by the specific context of Geopark Ijen, and results may vary in different settings.Originality/value—This research provides valuable insights into Instagram's role in promoting tourism destinations and supporting sustainable development. It highlights effective strategies for leveraging social media to enhance the visibility and attractiveness of unique natural and cultural sites. Future research could explore comparative analyses with other platforms and broader applications in different tourism contexts.